2020
DOI: 10.4251/wjgo.v12.i10.1119
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends of clinicopathologic features and survival duration after surgery for gastric cancer in Northeast China

Abstract: BACKGROUND Through analyzing the data from a single institution in Northeast China, this study revealed the possible clinicopathologic characteristics that influence the prognosis of patients with gastric cancer (GC). AIM To evaluate the changing trends of clinicopathologic features and survival duration after surgery in patients with GC in Northeast China, which is a high-prevalence area of GC. METHODS The study analyzed the difference in cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Meanwhile, there is no agreement on the accurate staging of GCC patients, though some studies have shown that GCC has a better prognosis than esophageal cancer when treated according to gastric cancer stages [ 32 ]. But some researchers did observe that the prognosis of GCC might be far worse than esophagus or other GC [ 33 , 34 ]. So, to explore and compare the potential prognostic difference between GC and GCC, we used the Chinses data and SEER data to conduct survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there is no agreement on the accurate staging of GCC patients, though some studies have shown that GCC has a better prognosis than esophageal cancer when treated according to gastric cancer stages [ 32 ]. But some researchers did observe that the prognosis of GCC might be far worse than esophagus or other GC [ 33 , 34 ]. So, to explore and compare the potential prognostic difference between GC and GCC, we used the Chinses data and SEER data to conduct survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no agreement on the accurate staging of GCC patients, but some studies have shown that GCC treated according to gastric cancer stages has a better prognosis than esophageal cancer [23]. Also, some researchers have observed that the prognosis of GCC might be far worse than esophagus or other GC [24,25]. So, to explore and compare the potential prognostic difference between GC and GCC, we used the Chinses data and SEER data to conduct survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy, radiotherapy, and traditional Chinese medicine can be used as auxiliary treatments. Clinically, for resectable STAD patients, the comprehensive treatment model based on surgical resection combined with chemotherapy has certain curative effects, but the tumor is prone to progress or relapse, and the 5-year survival rate of advanced STAD patients is as low as 10% to 15% [ 2 ]. For unresectable and metastatic STAD, patients can obtain limited benefit from typical therapies, including systemic chemotherapy and targeted drugs, but they are facing a larger treatment bottleneck, and the survival time of patients usually does not exceed 1 year [ 3 ].…”
Section: Introductionmentioning
confidence: 99%